Methodological problems in Serbian sociology - Analysis of the Sociološki pregled / Sociological review - Stojšin, Snežana S; Vidicki, Vladan D (Sociološki pregled, 2018)
The importance of consideration of some methodological issues in a science is one of the indicators of the degree to which it is developed. The assumption of this paper, which is derived from everyday contact with sociological literature, is that sociologists in Serbia pay little attention to methodological problems. Authors of this paper tried to point out the signifcance of methodological issues, conducting a content analysis of all the numbers of the “Sociološki pregled/ Sociological Review”, the frst sociological scientifc journal in Serbia.The results of the analysis show that the most fruitful period for methodological issues in Serbian sociology, at least by the frequency of publication of methodological papers, is located in the 70s of the last century. Also, the results show that the share of methodological articles in the total number of articles from the frst number to date is negligible (3,2%) and that much more attention is devoted to quantifcation than to qualitative research methods.
Keywords: Keywords; methodological issues; content analysis; Sociološki pregled/ Sociological Review; technical aspect; logical-epistemological problems